Pengaruh Pergantian Auditor, Kesulitan Keuangan, dan Reputasi KAP terhadap Fenomena Audit Delay - Gabriela Anjelin Ala; Minarni A. Dethan; Maria Indriyani H. Tiwu (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
The purpose of this study was to determine the effect of auditor switching, financial distress, and KAP reputation on the phenomenon of audit delay in property & real estate companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. This study uses three (3) independent variables, namely auditor switching, financial distress, and KAP reputation as well as one (1) dependent variable audit delay. The sampling method in this study used a purposive sampling technique with a sample of twenty-six (26) property & real estate companies listed on the Indonesia Stock Exchange for five (5) years of observation, in order to obtain a final sample of one hundred and thirty (130) data. The data analysis technique used is panel data regression analysis using the EViews 12 SV computer application program. The results of this study indicate that auditor switching and financial distress partially have no effect on audit delay. While the reputation of KAP partially affects the audit delay.